2022
DOI: 10.3390/microorganisms10101934
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Listeria monocytogenes Isolates Causing Three Different Clinical Outcomes

Abstract: Heterogeneity in virulence potential of L. monocytogenes subgroups have been associated with genetic elements that could provide advantages in certain environments to invade, multiply, and survive within a host. The presence of gene mutations has been found to be related to attenuated phenotypes, while the presence of groups of genes, such as pathogenicity islands (PI), has been associated with hypervirulent or stress-resistant clones. We evaluated 232 whole genome sequences from invasive listeriosis cases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…On the other hand, CC9 strains also presented a set of accessory genes including ami , encoding an autolytic amidase involved in the adhesion to eukaryotic cells, the teichoic acid biosynthesis associated gene tagB and the internalin genes inlG, inlL , and LIPI2_inlII. As reported by other studies, the inlG and inlL were lacking in lineage I strains [ 50 , 51 ]. A recent study by Gou et al 2022 [ 52 ] reported that the virulence of Lm strains during a mouse infection test decreased after the deletion of inlG , but the adhesion and invasion ability of these strains to Caco-2 cells was enhanced.…”
Section: Discussionsupporting
confidence: 76%
“…On the other hand, CC9 strains also presented a set of accessory genes including ami , encoding an autolytic amidase involved in the adhesion to eukaryotic cells, the teichoic acid biosynthesis associated gene tagB and the internalin genes inlG, inlL , and LIPI2_inlII. As reported by other studies, the inlG and inlL were lacking in lineage I strains [ 50 , 51 ]. A recent study by Gou et al 2022 [ 52 ] reported that the virulence of Lm strains during a mouse infection test decreased after the deletion of inlG , but the adhesion and invasion ability of these strains to Caco-2 cells was enhanced.…”
Section: Discussionsupporting
confidence: 76%
“…Recent studies highlighted differences in virulence among Lm strains based on the presence or absence of a truncated inlA gene, suggesting that the severity of illness should be considered when improving QMRA models using WGS data (Pouillot et al., 2015 ; Chen et al., 2020 ). Moreover, several studies reported differences in virulence between strains based on variations in lineages, serotypes and CCs (Nielsen et al., 2017 ; Fritsch et al., 2019 ; Maury et al., 2019 ; Quereda et al., 2021 ; Cardenas‐Alvarez et al., 2022 ; Muchaamba et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, ARG database searches often result in extensive lists of genes, which do not necessarily contribute to phenotypic resistance. By applying combined searches of databases (e.g., abricate and Resfinder) in combination with GWAS tools (e.g., gene- and k-mer based) a more comprehensive output can be generated ( Jaillard et al, 2018 ; Farhat et al, 2019 ; Bokma et al, 2021 ; Weber et al, 2021 ; Cardenas-Alvarez et al, 2022 ). Here, good predictive power was shown for 13 different antimicrobial drugs for which a non-WT population (ECOFF) was determined based on the NRI method for their AMR phenotypes.…”
Section: Discussionmentioning
confidence: 99%